Hidden lives : a family memoir - Forster, Margaret, 1938-2016 (Royal New Zealand Foundation of the Blind, 2013)
A memoir of the author's mother and grandmother including the search for the latter's illegitimate daughter. The book examines changes in work and family life over three generations.